Jekyll or Hyde? The genome (and more) of Nesidiocoris tenuis, a zoophytophagous predatory bug that is both a biological control agent and a pest - Ferguson, K B; Visser, S; Dalíková, M; Provazníková, I; Urbaneja, A; Pérez-Hedo, M; Marec, F; Werren, J H; Zwaan, B J; Pannebakker, B A; Verhulst, E C (Insect molecular biology, 2021)
Nesidiocoris tenuis (Reuter) is an efficient predatory biological control agent used throughout the Mediterranean Basin in tomato crops but regarded as a pest in northern European countries. From the family Miridae, it is an economically important insect yet very little is known in terms of genetic information and no genomic or transcriptomic studies have been published. Here, we use a linked-read sequencing strategy on a single female N. tenuis. From this, we assembled the 355 Mbp genome and delivered an ab initio, homology-based and evidence-based annotation. Along the way, the bacterial "contamination" was removed from the assembly. In addition, bacterial lateral gene transfer (LGT) candidates were detected in the N. tenuis genome. The complete gene set is composed of 24 688 genes; the associated proteins were compared to other hemipterans (Cimex lectularis, Halyomorpha halys and Acyrthosiphon pisum). We visualized the genome using various cytogenetic techniques, such as karyotyping, CGH and GISH, indicating a karyotype of 2n = 32. Additional analyses include the localization of 18S rDNA and unique satellite probes as well as pooled sequencing to assess nucleotide diversity and neutrality of the commercial population. This is one of the first mirid genomes to be released and the first of a mirid biological control agent.
Keywords: genom hmyzu; biologická ochrana; Animals; Gene Transfer, Horizontal; Genome, Insect; přenos genů horizontální; Female; symbióza; zvířata; biocontrol; Biological Control Agents; Hemiptera; linked-read; Symbiosis; Bacteria; ženské pohlaví; Heteroptera